Exposing Pelaku Bid and Run Pada Lelang Online Di Instagram Oleh Akun @gordonauction.Id; Studi Komparatif Antara UU ITE Dan Hukum Islam - Ibadurrahman Zaqi (Wasathiyyah, 2023)
In today's digital era, online auctions on platforms such as Instagram have become increasingly popular, offering convenience but also posing risks, including fraud, such as the "bid and run" practice that harms sellers. To address this issue, the online auction account @gordonauction.id exposes the details of perpetrators publicly on social media by sharing evidence of unresolved transactions. This action aims to deter offenders and warn other auction participants to act responsibly. This study seeks to examine the legality of exposing bid and run perpetrators by the Instagram account @gordonauction.id from both Islamic law and the Electronic Information and Transactions Law (UU ITE) perspectives. The focus of this research is on two main aspects: first, the Islamic legal perspective on the seller’s action of exposing bid and run perpetrators, and second, the perspective of UU ITE regarding such actions. This research adopts a qualitative approach with a descriptive case study design. Primary data is collected through interviews with the owner of the online auction account, bid and run perpetrators, and observations of auction activities on the @gordonauction.id account. Secondary data includes journals, theses, and articles related to bid and run. Data analysis is conducted using a descriptive approach. The findings indicate that, from an Islamic legal perspective, exposing bid and run perpetrators could be seen as tasyhīr (public exposure) intended to create deterrence. Meanwhile, under UU ITE, although this action could be considered defamation, it is justified as a means of protecting public interest and preventing further harm. This study is expected to provide a deeper understanding of the legality of exposing bid and run perpetrators in online auctions, as well as its contribution to legal protection in digital transactions.